Uncertainty of the Post-Covid Future: How will Humanity Solve this Puzzle (Global Journal of Management and Business Research, 2021)
The post-pandemic future is "shrouded" in complete uncertainty. Humanity is faced with COVID-19 in a situation where many economic and social problems have already accumulated, approaches to solving which have not been developed. At the same time, technological progress has brought humanity closer to fantastic prospects associated with the implementation of the achievements of the technological revolution 4.0. However, in this context, there has emerged and is growing the lack of professionals with relevant skills and competencies. In addition, the waves of the coronavirus pandemic, the emergence of more and more aggressive and deadly strains of it have dispelled the myth of humanity's ability to subordinate the eco-natural system to its interests without harming it. In a pandemic, the very organization of human society was under the threat of destabilization due to the violation of the dialectic of the relationship between individuals and society, citizens and the state, etc. The precariat, NEETs, generation Z with their specific preferences and value orientations became the result of a violation of the social integrity of national communities.